TYPES OF INDEPENDENT WORK OF STUDENTS IN THE LESSONS OF MATH IN THE ELEMENTARY CLASSES - Сеидли, Сабина (Pedagogy and Psychology, 2021)
The information age, unlike its predecessors, has brought about significant changes in our lives. In modern society, the rapid development of education is important. The article speaks of the close connection between education and life. It was noted that a requirement to meet the growing spiritual and material needs of people. Since the foundation of education is laid in the primary grades, teachers should pay great attention to the creative work of students, because new inventions, technological processing are the result of creative work. In fact, creative work is associated with the independent activity of people, as well as students. From this point of view, junior students should be provided with sufficient space for independent work. Of particular importance is the importance of independent work in mathematics lessons. The opinions of a number of scientists and methodologists on this issue are considered. Attempts have been made to find common ground in their approaches. The classifications of students' independent work are considered. Given that these classifications are based on different principles, the author presents his approach in the form of tables. The approximate schedule of time allocated for independent work has been investigated. It has been shown that this primarily depends on the level of knowledge of the class. Examples of assignments for two forms of independent work in the classroom are given. The differences between these types are explained. At the end, an experiment was carried out, the results of which showed that the applied method was justified. At the end, the didactic significance of the work is emphasized.